2017
DOI: 10.1007/s11306-017-1202-2
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics reveals a mild impact of remote ischemic conditioning on the plasma metabolome and α-hydroxybutyrate as a possible cardioprotective factor and biomarker of tissue ischemia

Abstract: IntroductionRemote ischemic conditioning (RIC) is a maneuver by which short non-lethal ischemic events are applied on distant organs or limbs to reduce ischemia and reperfusion injuries caused by e.g. myocardial infarct. Although intensively investigated, the specific mechanism of this protective phenomenon remains incompletely understood and in particular, knowledge on the role of small metabolites is scarce.ObjectivesIn this study, we aimed to study perturbations in the plasma metabolome following RIC and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Protective pathways of preconditioning-induced ischemic tolerance have been identified by transcriptomics, proteomics and metabolomics-based data sets (Stenzel-Poore et al, 2003 ; Scornavacca et al, 2012 ; Laursen et al, 2017 ). It is postulated that integration of RNA, protein and metabolite changes culminates in an ischemia tolerant cellular phenotype, yet few studies have attempted to identify the common pathways across omics platforms.…”
Section: Resultsmentioning
confidence: 99%
“…Protective pathways of preconditioning-induced ischemic tolerance have been identified by transcriptomics, proteomics and metabolomics-based data sets (Stenzel-Poore et al, 2003 ; Scornavacca et al, 2012 ; Laursen et al, 2017 ). It is postulated that integration of RNA, protein and metabolite changes culminates in an ischemia tolerant cellular phenotype, yet few studies have attempted to identify the common pathways across omics platforms.…”
Section: Resultsmentioning
confidence: 99%
“… 16 Cells were cultivated and subjected to 5.5-hrs simulated ischemia and 2 hrs reperfusion as previously described. 17 In short, the cells (~1x10 6 cells/well) were seeded into six-well plates (n=3-5 wells for each group) and cultivated for 48 hrs prior to induction of ischemia. Upon induction of ischemia, the growth medium was substituted by a stabilizing buffer solution (CaCl 2 : 1.25 mM, MgCl: 1mM, NaCl: 137 mM, KCl: 6 mM, Glucosemonohydrate: 10 mM, HEPES: 6 mM and NaH 2 PO 4 : 0.9 mM).…”
Section: Methodsmentioning
confidence: 99%
“…Exogenous application of nicotinamide mononucleotide (NMN), an intermediate of NAD + synthesis, mimics the protective effect of IPC under ischemia and reperfusion injury. An untargeted metabolomics study has revealed that α-hydroxybutyrate (α-HB) stands out as highly significantly upregulated after IPC [ 78 ], while previous studies have shown that an elevation in the cytosolic NADH/NAD + ratio would promote α-HB formation. α-HB is a biomarker of the cytosolic NADH/NAD + ratio [ 79 ], indicating that IPC can regulate the NADH/NAD + ratio.…”
Section: Metabolic Reprogramming In Ischemic Stroke Treatment By Ischemic Preconditioningmentioning
confidence: 99%